Cytotoxicity of Moringa Plants ( Moringa Oleifera L.) on Cancer Cells - Haryoto, Haryoto; Suranto, Choirun Nisa (Universitas Muhammadiyah Surakarta, 2024)
Moringa ( Moringa oleifera L.) is one of the herbal plants that grows in Indonesia. Moringa oleifera has many properties, namely that it can act as an antidiabetic, antibacterial, antitumor, antipyretic, antiepileptic, antiinflammatory, antiulcer, antispasmodic, diuretic, antihypertensive, cholesterol lowering, antioxidant, hepatoprotective, antifungal. The aim of preparing this review is to determine the cytotoxic activity of Moringa oleifera L.) and the mechanism of action of secondary metabolites that can be isolated from Moringa. The preparation of this review comes from articles obtained through the Google Scholar database , PubMed and Sciencedirect with the keywords namely